SINERGI KOLABORATIF MAHASISWA PBI DAN BK DALAM PENINGKATAN KOMPETENSI KEJURUAN DAN KETERAMPILAN PSIKOSOSIAL SISWA SMK ADI LUHUR JAKARTA - Nurmawati, Nurmawati; Rahmadina, Oktavia; Putri, Adisty Arya; Nurlaili, Risti; Putri, Nabila Rahma; Putri, Rena Ramadhona; Azmi, Fathiyah Nur (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This descriptive reflective study analyzes the collaborative synergy model of PBI and BK UHAMKA students at SMK Adi Luhur Jakarta. Through PLP documentation and observation, a Holistic Program Integration Model was identified, merging PBI and BK objectives. The model proved effective in enhancing vocational competency (English practice confidence) due to BK’s psychosocial support, while simultaneously improving psychosocial skills (motivation and self-awareness) through PBI’s vocational context. In conclusion, this cross-disciplinary synergy is crucial for comprehensive SMK education.